(untitled) (Journal of the College of Basic Education, 2022)
Reading comprehension constitutes one of the major goals in the language teaching program because of its relevance to develop a foreign language learners in their future life. As well as , it can be used as a mean to develop the skills of reading comprehension. English language learners in Iraq have an inadequate level of reading comprehension due to a number of factors such as the strategies and techniques they follow in their reading comprehension and the types of methods that the teachers use in teaching this skill. To achieve the aim of the present study, the researcher has used a new technique in teaching reading comprehension namely (number heads together) which is considered a new trend and the most important one in teaching and learning. To fulfill the aim of the study, a null hypothesis is postulated stating that there is no statistically significant difference between the mean scores of the students who are taught reading comprehension through using numbered heads together technique and those who are taught reading comprehension through using the technique recommended by the Teacher’s Guide. Ten weeks experiment was conducted utilizing and a pre- posttest experiment has been designed. Two sections were randomly selected from Zaho Al-lraq Secondary School for Girls. Sixty five/ fifth grade secondary female students were assigned to the experimental and control groups, 32 students were for the experimental group and 33 students were for the control group after excluding five students from both groups, because they were repeaters in this grade. Both groups were statistically equalized in a number of variables such as age , parents’ level of education, students ’scores in English in the previous year, and the students’ scores obtained in the pre test. The experimental group had been taught reading comprehension by using numbered head together technique whereas the control group was taught by the classical teaching method ( i.e., currently followed method). After the administration of the tests to the main samples and the statistical treatment of data using the t-test for two independent samples, the experimental group scores outperformed the control groups scores. These results referred to the effectiveness of using number head together technique in teaching reading comprehension skills. In the light of the results, a number of conclusions, recommendations and suggestions for further research were stated.